Beneath the glitter and chaos thinking on and teaching with Philippine culture and society - Reyes, Soledad S. (2020)
This paper examines the ways in which popular texts have been perceived in the Philippines and explores the reasons for their denigration in academe for decades. The discussion attempts to show how the events of the late 1960s and 1970s marked a change in the way such texts as films, komiks and theatrical performances could be studied from a vareity of approaches beyond Formalism and Marxism. The paper also proposes ways this field of study can be mined in the classroom as a way of developing critical thinking among students.
Keywords: Komiks; Philippine cultural studies; Philippine films